2016
DOI: 10.1016/j.cellsig.2016.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Glucosamine induces REDD1 to suppress insulin action in retinal Müller cells

Abstract: Resistance to insulin action is a key cause of diabetic complications, yet much remains unknown about the molecular mechanisms that contribute to the defect. Glucose-induced insulin resistance in peripheral tissues such as the retina is mediated in part by the hexosamine biosynthetic pathway (HBP). Glucosamine (GAM), a leading dietary supplement marketed to relieve the discomfort of osteoarthritis, is metabolized by the HBP, and in doing so bypasses the rate-limiting enzyme of the pathway. Thus, exogenous GAM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
(57 reference statements)
1
11
0
Order By: Relevance
“…6 ). Consistent with our results, independence of O-GlcNAcylation from tissue injury was also shown in retinal neurons ( Nakamura et al , 2001 ) as well as retinal Mueller cells ( Moore et al , 2016 ) when they were exposed to GlcN.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…6 ). Consistent with our results, independence of O-GlcNAcylation from tissue injury was also shown in retinal neurons ( Nakamura et al , 2001 ) as well as retinal Mueller cells ( Moore et al , 2016 ) when they were exposed to GlcN.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, although GlcN was found to be toxic to cultured motor neurons ( Lim et al , 2010 ), its relationship to diabetic neuropathy has not been adequately addressed. Interestingly, some studies have connected endoplasmic reticulum (ER) stress with HBP and the genesis of diabetic complications ( Werstuck et al , 2006 ; Moore et al , 2016 ). A role for ER stress in the development of neuropathy was confirmed by several laboratories using streptozotocin-induced diabetic rats and CCAT-enhancer-binding protein-beta CCAT-enhancer-binding homologous protein (CHOP)-deficient mice ( Lupachyk et al ., 2013 ; Wu et al ., 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that REDD1 acts to modulate site-specific activity of PP2A, although how it does so remains unclear. It is noteworthy that recent work by Moore and coworkers demonstrated the ability of glucosamine to repress insulin-stimulated PKB/Akt Thr308 phosphorylation and downstream mTORC1 signalling in retinal Müller cells by increasing ER stress and REDD1 protein expression [29]. However, the potential involvement of PP2A in mediating the insulin-desensitising action of glucosamine was not determined in this study.…”
Section: Regulation Of Insulin Sensitivity By Redd1mentioning
confidence: 63%
“…However, there are little data regarding the side effects of GlcN supplementation on metabolic or vascular systems. It was reported that GlcN promotes endoplasmic reticulum stress in retinal Müller cells and leads to the resistance to insulin action, suggesting that GlcN potentially exacerbates diabetes-induced hyperglycaemia 40 . Another study also indicated that GlcN enhanced insulin resistance in mice fed a normal diet but ameliorated obesity and insulin resistance in mice fed a high-fat diet 41 .…”
Section: Discussionmentioning
confidence: 99%